Rapid force generation during unilateral isometric hamstring assessment: reliability and relationship to maximal force - Ripley, N. J.; Fahey, J.; Cuthbert, M.; McMahon, J. J.; Comfort, P. (Sports Biomechanics, 2023)
Limited research has reported the reliability of rapid force generation characteristics during isometric assessments of the hamstrings. Therefore, the purpose of the present study was to determine the between-session reliability of rapid force generating characteristics of the hamstrings and relationship to maximal force production. Twenty-three female soccer players (age: 20.7 ± 4.7 years; height: 168.7 ± 5.9 cm; body mass: 64.4 ± 6.7 kg) performed three unilateral trials of the 90-90 isometric hamstring assessment, on two separate occasions, separated by 7 days. Peak force, force at 100- and 200 ms and average rate of force development (aRFD) over 100- and 200 ms epochs were calculated. Absolute and fair-good reliability was observed for peak force and all rapid force generating measures (<8.33CV%, ICC >0.610). Significant and meaningful relationships (p < 0.001, r > 0.802) were observed for all rapid force generating measures and peak force. The 90-90 isometric assessment can be used to assess peak and rapid force generating reliably to enable practitioners to confidently track changes in performance over time as part of fatigue monitoring and management.